FACTORS AFFECTING CREDIT DISTRIBUTION OF BANKING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Gunawan, Audrey Valencia; Sufiyati , Sufiyati (International Journal of Application on Economics and Business, 2023)
The aim of this research is to examine whether CAR, LDR, BOPO, TPF, NPL and ROA influence credit distribution in banking sector companies listed on the IDX for the 2018-2020 period. 41 banking companies were used as research samples based on sample criteria. Data was obtained using IBM SPSS Statistics 26 software. The research results show that CAR has a significant negative effect on Credit Distribution. LDR and TPF have a significant positive effect on Credit Distribution. BOPO does not have a significant negative effect on Credit Distribution. NPL and ROA do not have a significant positive effect on Credit Distribution.